Angkatan Kerja dan Faktor yang Mempengaruhi Pengangguran - Adriyanto Adriyanto; Didi Prasetyo; Rosmiyati Khodijah (Universitas Musamus,Merauke,Papua, 2020)
This writing is a study of the number of labor force and unemployment which aims to see the employment relationship and the factors that affect the unemployment rate. The method used is descriptive qualitative. The results showt that potentially, Indonesia has human resource capabilities to be developed and in other parties are faced problems of manpower fields. The development of the number of labor force is rapid but not followed by sufficient employment opportunities. Another obstacle is the supply of labor that is not in accordance with the needs or certain qualifications demanded by the labor market even though the demand is very high, which causes higher unemployment. The minimum wage also greatly affects the unemployment rate. The wages set by the government greatly affect the existing unemployment rate. Any increase in the wage rate will be followed by a fall in the workforce that follows, which means unemployment. It is hoped that the Government's commitment to increase the opening of new jobs that can absorb a large number of workers to reduce the unemployment rate which has implications for signs of the poverty rate.